Histological aspects of the digestive system Alpaca - De la Vega D., Elmo (1952)
The present article deals with the anatomical study of the digestive system in 11 Alpacas ("Lama glama pacos"). The author has made the microscopical studies on the digestive system and claims that in the proventriculi of such animals there is a variation on the structure in relation with the other domestic rumiants. The author ilustrates with good number of microphotographies.